2015
DOI: 10.1371/journal.ppat.1004699
|View full text |Cite
|
Sign up to set email alerts
|

Direct Binding of Retromer to Human Papillomavirus Type 16 Minor Capsid Protein L2 Mediates Endosome Exit during Viral Infection

Abstract: Trafficking of human papillomaviruses to the Golgi apparatus during virus entry requires retromer, an endosomal coat protein complex that mediates the vesicular transport of cellular transmembrane proteins from the endosome to the Golgi apparatus or the plasma membrane. Here we show that the HPV16 L2 minor capsid protein is a retromer cargo, even though L2 is not a transmembrane protein. We show that direct binding of retromer to a conserved sequence in the carboxy-terminus of L2 is required for exit of L2 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
197
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(209 citation statements)
references
References 55 publications
12
197
0
Order By: Relevance
“…Regardless, our data suggest that the L2 protein is important for directing the HPV-containing membranous structures toward the nucleus during mitosis. It was recently demonstrated that the L2 protein becomes transmembranous to engage numerous cytoplasmic factors required for trafficking to the TGN and possibly the ER, with some 30 N-terminal residues being luminal (28,32). We have shown that L2 assumes a similar topography during mitosis, suggesting that HPV-harboring vesicles bud out of the TGN or the ER during the onset of mitosis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Regardless, our data suggest that the L2 protein is important for directing the HPV-containing membranous structures toward the nucleus during mitosis. It was recently demonstrated that the L2 protein becomes transmembranous to engage numerous cytoplasmic factors required for trafficking to the TGN and possibly the ER, with some 30 N-terminal residues being luminal (28,32). We have shown that L2 assumes a similar topography during mitosis, suggesting that HPV-harboring vesicles bud out of the TGN or the ER during the onset of mitosis.…”
Section: Discussionmentioning
confidence: 86%
“…Host cell cyclophilins release the majority of L1 from the L2 protein, which remains in complex with the viral genome (2,23,24). A large portion of the L2 protein translocates across the endocytic membrane to engage factors, including the retromer complex, dynein, sorting nexins, and rab GTPases, that mediate transport to the trans-Golgi network (TGN) (25)(26)(27)(28)(29)(30)(31)(32)(33)). An siRNA screen has suggested that nuclear pore complexes are not required for nuclear entry, but that nuclear envelope breakdown during mitosis is necessary (34,35).…”
mentioning
confidence: 99%
“…Subsequently, PLA was performed according to the manufacturer's instructions (Olink Bioscience), except that only an anti-rabbit minus probe was used. Quantification of the PLA signal was performed as previously described (Popa et al 2015). For immunofluorescence, HeLa cells were prepared without transfection, and the secondary antibody used was 1:1000 diluted Alexa fluor 594 goat anti-rabbit (Invitrogen).…”
Section: Pla Immunofluorescence Analysis and Antibodiesmentioning
confidence: 99%
“…Interactions of L2 with actin (40), components of the retrograde transport machinery (37,41,42), sorting nexins 17 and 27, TSG101, ␥-secretase, and Hsc70, as well as the microtubule network, have been reported (37,(41)(42)(43)(44)(45)(46)(47)(48). These interactions result in trafficking to the Golgi network (37,41,42,47), transport toward the nucleus (43,44), and accumulation at nuclear substructures (49)(50)(51)(52)(53). Furthermore, L2 possesses a membrane-destabilizing peptide in its C terminus (54) and a transmembrane domain in its N terminus (55) that are both important for translocation to the cytoplasm.…”
mentioning
confidence: 99%